Contributions, challenges, and emerging patterns of short-term missions - Twibell, Simone Mulieri (Missiology, 2020)
It was not until the last decade that missiologists placed the short-term missions (STM) movement at the center of their research. As the initial wave of STM scholarship surfaced, research centered on measuring the impact of STM on participants. Later, attention shifted to unraveling the impact upon the host community. More recently, with the exponential growth of partnerships between congregations in the Global North and the South, researchers have focused on analyzing the prevalent dynamics and patterns of relationships that involve STM teams. This article unravels the impact of STM in terms of its contributions and challenges to the global missionary enterprise and describes emerging patterns, such as reverse STM and multicultural STM teams.